Limites da atuação da Comissão de Valores Mobiliários na regulação dos fundos de investimento - Mariana Loyola Ferreira (2014)
The purpose of this study is to investigate the limits of the performance of the Brazilian Securities and Exchange Commission in the regulation of investment funds concerning not only the analysis of the structure and legal rules governing the investment funds but also the performance of the Securities Commission as regulatory Agency, in order to identify the limitations that regulation , can impose to investment funds and the uncertainty that reaches the agents of the capital market in the Brazilian legal system. Initially, it presents basic concepts on the Brazilian financial market. Subsequently, it studies the institute of the investment funds, bringing up its main characteristics, its legal system and the doctrinal debate about its legal nature. After the presentation of the market in which they operate and its main features, it seeks to analyze the regulation of the Brazilian capital market and the role of the Brazilian Securities Commission in regulating securities. Then, it focuses on the legal concept of securities in which the investment funds can be inserted in order to present the limitations caused by the CVM on such a concept. It finally shows how they limit the actual performance of the regulator about the institute.